7(6+3x)=105A

Simple and best practice solution for 7(6+3x)=105A equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(6+3x)=105A equation:


Simplifying
7(6 + 3x) = 105A
(6 * 7 + 3x * 7) = 105A
(42 + 21x) = 105A

Solving
42 + 21x = 105A

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + 21x = -42 + 105A

Combine like terms: 42 + -42 = 0
0 + 21x = -42 + 105A
21x = -42 + 105A

Divide each side by '21'.
x = -2 + 5A

Simplifying
x = -2 + 5A

See similar equations:

| 5y-3=-15 | | 25x+0.6=-30 | | 2q^2-12q=0 | | 2b+-8=2 | | 36+7n=6(5n+6)+3n | | 2(8m+3)=54 | | 2y+2=4x-2 | | 4z-7=11-2z | | 3a+2b-8a-3b= | | 7y-9=4y-12 | | 5r+20-7r=-16 | | -12-2x=-2(x+5) | | s=550 | | 6x+8x+10x=180 | | 12=3(6t+1) | | -2.8=-0.56(m+8) | | 7(4y-5)+3(5y+4)= | | 3m-17=52 | | 3(6x+24)=18x+72 | | 2q(q-6)=0 | | 2=2v-2 | | 6(1-4y)-5y=-8(3+4y) | | 6x+9y=2 | | 2k-4=12 | | 4-3x=-3+4x | | 3.5x+1.25= | | -25k=-150 | | 82=-65-x | | -(7x+6)=-3(1+2x) | | 4m^2-12a=-8 | | 7b+3-4b=3-3(-b+4) | | 7x+9-3x=25 |

Equations solver categories